The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1984-6487.sess.2018.30.02.a
|View full text |Cite
|
Sign up to set email alerts
|

Prostitución y feminismo(s). Disputas por el reconocimiento en los Encuentros Nacionales de Mujeres (Argentina, 1986-2017)

Abstract: Resumen La “prostitución” es una de las grandes preocupaciones del feminismo, y la postura en relación a la misma ha polarizado a las feministas como casi ninguna otra cuestión. En Argentina, este debate tuvo como uno de sus primeros escenarios al Encuentro Nacional de Mujeres (ENM), que se realiza todos los años desde 1986, nucleando a miles de mujeres, algunas de las cuales se identifican en distintos grados con el feminismo -esto varía de año a año- y que por tres días discuten las problemáticas que conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Even constituting a minority, they verbalized affective-emotional lexicons, such as sadness, stress and anxiety, revealing that happiness is a feeling somewhat distant from the reality experienced by them. Such representations can be verified in the results of other studies, which associated the conditions of the profession and life of many of them with physical and psychological abuse and submission to men ( 25 - 26 ) .…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Even constituting a minority, they verbalized affective-emotional lexicons, such as sadness, stress and anxiety, revealing that happiness is a feeling somewhat distant from the reality experienced by them. Such representations can be verified in the results of other studies, which associated the conditions of the profession and life of many of them with physical and psychological abuse and submission to men ( 25 - 26 ) .…”
Section: Discussionsupporting
confidence: 61%
“…Thus, several professionals reported that the act of performing the sexual service is linked to the difficulties they face on a daily basis, namely: economic, family, integration into the formal job market, few years of study and affective aspects. This issue is reaffirmed by a study carried out in Iran, which reported the deficit of opportunities distributed by state power, resulting in a state of extreme poverty, being a preponderant factor for the search for subsistence with sex work (8,25,27) .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Mesmo constituindo uma minoria, verbalizaram léxicos afetivos--emocionais, como tristeza, estresse e ansiedade, revelando que a felicidade é um sentimento um tanto longíquo da realidade vivenciada por elas. Tais representações podem ser verificadas em resultados de outros estudos, que associaram as condições da profissão e da vida de muitas delas ao abuso físico, psicológico e à submissão aos homens (25)(26) .…”
Section: Discussionunclassified